2013
DOI: 10.1186/2042-6410-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Advancing sex and gender competency in medicine: sex & gender women's health collaborative

Abstract: Research conducted to date has deepened our understanding of sex and gender differences in the etiology, diagnosis, treatment, and outcomes for many conditions that affect both women and men. The Sex and Gender Women’s Health Collaborative (SGWHC) is supported by the coordinated efforts of our founding partners: the American Medical Women’s Association, the American College of Women’s Health Physicians and Society for Women’s Health Research to address the gaps in medical education with regard to sex and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…2 Sex differences result from true biological differences in the structure and function of the cardiovascular systems of men and women. In contrast, gender differences ensue from a person’s self-representation resulting in psychosocial roles and behaviors imposed by society; gender implies social roles, behaviors, and cultural norms.…”
mentioning
confidence: 99%
“…2 Sex differences result from true biological differences in the structure and function of the cardiovascular systems of men and women. In contrast, gender differences ensue from a person’s self-representation resulting in psychosocial roles and behaviors imposed by society; gender implies social roles, behaviors, and cultural norms.…”
mentioning
confidence: 99%
“…The task force conducted a needs assessment involving the medical education literature, medical school faculty, and medical students to gauge the gaps between curriculum goals and student outcomes. A review of the medical education literature showed that medical professionals' lack of understanding and consideration regarding sex and gender differences in etiology, pathology, presentation, and treatment response has become a major concern in health science education and practice (Baggio, Corsini, Floreani, Giannini, & Zagonel, 2013;McGregor, Templeton, Kleinman, & Jenkins, 2013). Experts in clinical medicine underscore the importance of health professionals understanding differences in sex (biological) and gender (socio-cultural) in the clinical care process to improve healthcare outcomes for patients.…”
Section: Project Planning Need Assessment and Goalsmentioning
confidence: 99%
“…Although the field of women's health has historically addressed both sex and gender in its clinical and research efforts, considering the roles of sex and gender more broadly (rather than focusing on female sex or gender alone) allows more meaningful exploration of the physiologic and behavioral mechanisms involved in sex and gender differences (Miller, 2014). By illustrating the implications of these differences for health and disease, such an approach can advance science and improve the health of all individuals (McGregor, Kleinman, & Jenkins, 2013). However, both women's health and broader sex-and gender-informed initiatives require approaches integrated sufficiently to engage with and support translation of evidence to other disciplines, yet distinct enough to allow development of deep research and clinical expertise, obtain targeted funding, and advocate for changes in policy and practice.…”
Section: What Is Sex-and Gender-informed Medicine?mentioning
confidence: 99%